Analisis Pengaruh Current Ratio (CR) Dan Debt To Equity Ratio (DER) Terhadap Pertumbuhan Laba Pada PT. Jasa Marga Tbk - Muhammad Windras; Nafisah Nurul Rahmatiah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine and analyze the influence of the Current Ratio and Debt to Equity Ratio on profit growth. This research method uses quantitative methods. The data collection method uses secondary data. The sample technique uses Purposive Sampling. The population in this study were a number of PT financial reports. Jasa Marga Tbk for 15 years, starting from 2007 - 2021, and the sample used was 10 years from 2012 - 2022. Based on the results of this research, it shows that partially the variables Current Ratio (X1) and Debt to Equity Ratio (X2) have no effect on profit growth.